Intestinal parasitic infections: Current status and associated risk factors among school aged children in an archetypal African urban slum in Nigeria - Vincent P. Gyang; Ting-Wu Chuang; Chien-Wei Liao; Yueh-Lun Lee; Olaoluwa P. Akinwale; Akwaowo Orok; Olusola Ajibaye; Ajayi J. Babasola; Po-Ching Cheng; Chia-Mei Chou; Ying-Chieh Huang; Pasaiko Sonko; et al. (Journal of Microbiology, Immunology and Infection, 2019)
Background/purpose: Intestinal parasitic infections (IPIs) among school aged children (SAC) in Nigeria remains endemic, hence the need for regular surveillance to attract the attention of policy makers. This cross-sectional study investigated the current prevalence and factors associated with intestinal parasitic infections among school aged children in an urban slum of Lagos City, Nigeria. Methods: Single stool samples from 384 school aged children (188 boys and 196 girls) were examined by employing Merthiolate-iodine-formaldehyde concentration (MIFC) and Kato-Katz methods. Demographic characteristics and risk factors were obtained by questionnaires investigation. Results: The overall prevalence was 86.2% in school children, out of them 39.1% had polyparasitism. IPIs showed the highest to the lowest prevalence of 62% (238/384), 25% (97/384), 12.3% (47/384), 11.8% (45/384), 9.9% (38/384), 8.4% (32/384), 3.4% (13/384), and 0.5% (2/384) found in Ascaris lumbricoides, Entamoeba histolytica/dispar, Giardia duodenalis, Endolimax nana, Entamoeba coli, Trichuris trichiura, Blastocystis hominis, and hookworm infections, respectively. MIFC technique showed superiority to Kato-Katz technique in the detection of IPIs (p < 0.0001). Drinking untreated water was a significant risk factor for these school aged children in acquiring protozoan infections after multivariate adjustment (OR = 1.86, 95% CI = 1.08–3.20, p = 0.02). Conclusion: Intestinal parasitic infections are very severe among school aged children in the urban slums, thus regular mass de-worming programs, health education, and the provision of safe drinking water is recommended to combat IPIs among the school aged children. Keywords: Intestinal parasitic infections, Prevalence, Risk factors, Schoolchildren, Slum, Nigeria